0.5 Gy confers resistance to a subsequent high dose of γ-rays by modulating HO-1/Nrf2 and apoptosis pathways - Yasser F. Ali; Ibrahim M. Hassan; Hussein M. Abdelhafez; Omar S. Desouky (Scientific Reports)
Abstract Ionizing radiation, from the DNA centric view, elicits biological effects and health consequences solely through energy deposition events in the cell nucleus. At higher radiation doses, this is likely true; however, at low doses, non-targeted effects, a subcategory of which is the adaptive response, tend to dominate. Controversies exist over the definition of low dose. From a radiation therapy view, it is defined as 0.5–0.7 Gy. Therefore, we investigated the effects of exposure to ionizing radiation with or without a 0.5 Gy priming dose. Techniques including comet assay, flow cytometry, fluorescence microscopy, and real-time quantitative PCR were employed. In normal lung fibroblasts (WI-38), there was a statistically significant difference in mean normalized tail moments when comparing treatment with the challenge dose alone to treatment with a 0.5 Gy priming dose prior to the challenge dose (P < 0.05). Moreover, pretreatment with a 0.5 Gy priming dose reduced G1 phase cell cycle arrest and cell death—either through apoptosis or mitotic catastrophe—induced by the subsequent 2 Gy exposure. Similarly, A549 Cells pre-exposed to a 0.5 Gy priming dose before a 2 Gy exposure showed a lower percentage of apoptosis than those exposed to the 2 Gy alone. Mechanistically, cells responded to a priming 0.5 Gy by increasing the expression of HMOX1, SOD, and Bcl2 while decreasing of IL-1β and TNF-α. In conclusion, 0.5 Gy induces an adaptive response in lung normal and cancer cell against subsequent high doses of γ-rays. Modulation of the HO-1/Nrf2 and apoptosis pathways underlie the resistance observed in primed cells.